The Importance of Ecological Tourism in the Context of Hotel and Restaurant Business Management in the Conditions of Stability of Ecosystems of Territories - Liudmyla NESHCHADYM; Svitlana TYMCHUK; Liubov KOVALENKO; Diana NAHERNIUK; Valentyna NEPOCHATENKO; Svitlana PODZIHUN (Communications of International Proceedings, 2020)
This article examines the comprehensive implementation of the concept of sustainable development, helps to make eco-tourism more important every year. An important goal of this article is the efficient and rational use of resource potential and the optimal solution of regional development problems. The ecotourism industry performs important functions in the development of the economic complex and economy of the country, district, region as it increases local incomes; creates new jobs; promotes the development of industries focused on the production of ecotourism services; develops social and production infrastructure in tourist centers; increases budget revenues. Entrepreneurs’ interest in ecotourism can be explained by a number of factors: in order to start an ecotourism business, you do not need large financial investments; in the market of ecotourism services, despite the competition, both large and medium and small companies and firms can successfully interact; ecotourism business allows you to quickly turn capital. The results of environmental activities are assessed by ecological and economic efficiency. The concept of ecological efficiency includes reclaimed land and disturbed landscapes, planted forest areas instead of cut down or killed by acid rain, contaminated groundwater, frost, hurricanes, felling of diseased trees and shrubs, restored meadows and forest litter, conservation and reproduction of rare species of flora and fauna and other restorative measures. The main indicator of ecological efficiency of environmental measures in relation to recreational resources is the possibility of their use for their intended purpose with the subsequent receipt of economic benefits.
Keywords: Tourism; Ecology; Ecological Tourism; Business; Development; Economy.